DJ-1 mutations in Parkinson's disease. Issue 1 (5th January 2004) - Healy, D G; Abou-Sleiman, P M; Valente, E M; Gilks, W P; Bhatia, K; Quinn, N; Lees, A J; Wood, N W
Abstract : Mutations in the DJ-1 gene have recently been shown to cause autosomal recessive Parkinson's disease. To estimate the prevalence of this mutation, an analysis was undertaken of 39 index cases of Parkinson's disease in whom a family history suggested autosomal recessive inheritance. No DJ-1 mutations were found in these patients, indicating that this gene is unlikely to be of numerical significance in clinical practice. The hypothesis was also tested that young onset Parkinson's disease patients in whom, despite extensive analysis, only a single heterozygous parkin mutation was found, might harbour a second mutation in the DJ-1 gene—that is, digenic inheritance. No patient was found with a single mutation in both DJ-1 and parkin genes, making this mode of inheritance unlikely. Finally it was confirmed that PARK6 and PARK7 (DJ-1), despite being phenotypically similar and mapping to the same small chromosomal region of 1p36, are caused by mutations in separate genes.